1984
DOI: 10.1182/blood.v63.2.384.384
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic cell differentiation in vivo and in vitro: arrest of proliferation parallels the differentiation induced by the antileukemic drug Harringtonine

Abstract: A variety of chemical agents have been shown to induce differentiation in in vitro cultured neoplastic cell lines. We noted that blast cells in the peripheral blood of acute nonlymphoid leukemia patients treated with the drug Harringtonine appeared to undergo morphological changes that suggested differentiation. In view of the relatively minimal myelotoxicity of Harringtonine, we hypothesized that harringtonine was acting by differentiation-induction, which concomitantly arrested cell division. We tested this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…triggering apoptosis [33,34]. However, patients often fail to undergo complete remission as a result of the occurrence of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…triggering apoptosis [33,34]. However, patients often fail to undergo complete remission as a result of the occurrence of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in IL-18R levels, particularly in response to differentiation induction, further provides a stronger antiapoptotic effect in anticancer drug-treated AML cells. However, this suggestion needs to be further verified in vitro and clinically for AML patients treated with anticancer drugs, such as VitD3, harringtonine, and bufalin [33,34], which are involved in the induction of differentiation activity.…”
Section: Discussionmentioning
confidence: 99%
“…As an initial step in attempting to analyse the effect of ARA-C on patients' leukaemic cells, its action on this cloned cell line was studied. The FCS used in this study was optimized for growth rate, and the doubling time was estimated to be approximately 30 h. The effect of ARA-C was compared with that of Harringtonine (Harr) which we have shown induced monocytic differentiation in HL60 cells (Boyd & Sullivan, 1984). Liquid cultures ( lo5 cells/ml) were established in the presence of ARA-C, Harr or TPA and incubated for 4 d. The cells were then analysed for morphology and non-specific esterase staining.…”
Section: Eflect Of Ld Ara-c On Hl60mentioning
confidence: 99%
“…The dose-response curve of DNA synthesis inhibition as reported by others (Harris et al, 1979) would tend to favour a differentiation role for LD ARA-C (Cataigne et al, 1983). Indeed we have shown that the predominant mode of action of the antileukaemic drug Harringtonine is by differentiation induction (Boyd & Sullivan, 1984).…”
mentioning
confidence: 99%
“…Of seven antitumor agents tested in vitro in a human cell line, none was synergistic with HHT [6]. The HL60 human promyelocytic leukemia cell line is sensitive to and undergoes differentiation in the presence of low levels of HHT [7,8].…”
Section: Introductionmentioning
confidence: 99%